(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
The article presents the results of a study of some physiometric parameters in urban school students. It studied the functional parameters of the cardiovascular and respiratory systems in 11, 16 and 18-year-old schoolchildren, as well as the Rufye test, the adaptive potential of the circulatory system. The results obtained were compared with the standard sizes and appropriate conclusions were drawn. The study provides recommendations for improving students’ physical development and health